Juvenile cataract in association with tuberous sclerosis complex. (3rd July 2020) - Geffrey, A. L.; Geenen, K. R.; Abati, E.; Greenstein, S. H.; VanderVeen, D. K.; Levy, R. L.; Davidson, S. L.; McGarrey, M. P.; Thiele, E. A.; Aronow, M. E.
ABSTRACT: Background: Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder characterized by benign hamartomas occurring in multiple organ systems including the brain, kidneys, heart, lungs, liver, skin, and the eyes. Typical retinal findings associated with TSC include astrocytic hamartoma and achromic patch. While rare cases of cataract occurring in the setting of TSC have been reported, this is the first analysis of a large series of individuals with TSC that aims to quantify the frequency of this finding and to describe its clinical and genetic associations. Materials and Methods: This is a retrospective chart review of 244 patients from the Herscot Center for Tuberous Sclerosis Complex at the Massachusetts General Hospital who underwent complete ophthalmic examination. We describe the clinical and genetic findings in five individuals with TSC and juvenile cataract. Results: Four of five cases (80%) were unilateral. The cataract was described as having an anterior subcapsular component in 3 of 5 cases (60%). Three individuals (60%) underwent lensectomy with intraocular lens (IOL) implant and two individuals (40%) were observed. Genetic testing revealed a known disease-causing mutation in TSC2 in 100% of cases. Conclusions: Recent evidence suggests that mTOR signaling may play a role in cataract formation which could explain the relatively high incidence of juvenile cataract in this population. Juvenile cataract is a potentially under-recognized ocular manifestation of TSC.